MMP‐7 affects peritoneal ultrafiltration associated with elevated aquaporin‐1 expression via MAPK/ERK pathway in peritoneal mesothelial cells. Issue 14 (11th June 2021) - Yin, Yue; Zhang, Fen; Zheng, Zhuojun; Xiao, Zhiwen; Yang, Qiaomu; Gong, Nirong; Zhou, Jia; Zuo, Daming; Ai, Jun
Abstract: Peritoneal membrane dysfunction and the resulting ultrafiltration failure are the major disadvantages of long‐term peritoneal dialysis (PD). It becomes increasingly clear that mesothelial cells play a vital role in the pathophysiological changes of the peritoneal membrane. Matrix metalloproteinases (MMPs) function in the extracellular environment of cells and mediate extracellular matrix turnover during peritoneal membrane homeostasis. We showed here that dialysate MMP‐7 levels markedly increased in the patients with PD, and the elevated MMP‐7 level was negatively associated with peritoneal ultrafiltration volume. Interestingly, MMP‐7 could regulate the cell osmotic pressure and volume of human peritoneal mesothelial cells. Moreover, we provided the evidence that MMP‐7 activated mitogen‐activated protein kinases (MAPKs)‐extracellular signal‐regulated kinase 1/2 (ERK) pathway and subsequently promoted the expression of aquaporin‐1 (AQP‐1) resulting in the change of cell osmotic pressure. Using a specific inhibitor of ERK pathway abrogated the MMP‐7‐mediating AQP‐1 up‐regulation and cellular homeostasis. In summary, all the findings indicate that MMP‐7 could modulate the activity of peritoneal cavity during PD, and dialysate MMP‐7 might be a non‐invasive biomarker and an alternative therapeutic target for PD patients with ultrafiltration failure.